Bioaccesibility of Cylindrospermopsin from cooked fish muscle after the application of an in vitro digestion model and its bioavailability. (December 2017) - Maisanaba, Sara; Saladino, Federica; Font, Guillermina; Jos, Ángeles; Cameán, Ana M.; Meca, Giuseppe
Abstract: Humans can be exposed to cyanotoxins through the ingestion of contaminated water, food or beverages. In the present work, the bioaccesibility of Cylindrospermopsin (CYN), one of the most relevant cyanotoxins, was evaluated in a pure CYN solution and cooked CYN-contaminated fish muscles (20 μg/mL). An in vitro digestion model including the salivar, gastric, duodenal and colonic phases was performed, being each fraction analyzed by HPLC-MS-MS to evaluate CYN degradation. Moreover, Caco-2/TC7 cells were exposed to the digested duodenal and colonic phases to elucidate the final bioavailability of CYN in an approximation to the real human exposure scenario. The results revealed that CYN bioaccesibility decreased after the digestive process in all the cooked fish samples. The most drastic reductions were observed after lactic acid bacteria exposure. Thus, the highest bioaccesibility values were obtained in fish cooked by steaming (12.5%) and broiling (10.9%) meanwhile CYN was not detected in the colonic phase after boiling and microwaving. Regarding the duodenal and colonic availability, only in CYN pure digested solution the cyanotoxin was identified. The results obtained showed that digestion processes plays a very important role in the degradation of CYN, which should be considered when preparing a risk assessment of CYN. Highlights: The bioaccesibility of CYN in fish cooked muscle has been studied for the first time. A decrease of CYN bioaccesibility was observed after the in vitro digestion process. The colonic phase induced the most relevant diminution in CYN bioaccesibility. The bioavailabilty of CYN was studied in Caco-2/TC7 cells.